Revisiting Astrocytic Roles in Methylmercury Intoxication - Arrifano, Gabriela de Paula; Augusto-Oliveira, Marcus; Souza-Monteiro, José Rogério; Macchi, Barbarella de Matos; Lima, Rafael Rodrigues; Suñol, Cristina; do Nascimento, José Luis Martins; Crespo-Lopez, Maria Elena (Molecular neurobiology, 2021)
Intoxication by heavy metals such as methylmercury (MeHg) is recognized as a global health problem, with strong implications in central nervous system pathologies. Most of these neuropathological conditions involve vascular, neurotransmitter recycling, and oxidative balance disruption leading to accelerated decline in fine balance, and learning, memory, and visual processes as main outcomes. Besides neurons, astrocytes are involved in virtually all the brain processes and perform important roles in neurological response following injuries. Due to astrocytes’ strategic functions in brain homeostasis, these cells became the subject of several studies on MeHg intoxication. The most heterogenous glial cells, astrocytes, are composed of plenty of receptors and transporters to dialogue with neurons and other cells and to monitor extracellular environment responding tightly through fluctuation of cytosolic ions. The overall toxicity of MeHg might be determined on the basis of the balance between MeHg-mediated injury to neurons and protective responses from astrocytes. Although the role of neurons in MeHg intoxication is relatively well-established, the role of the astrocytes is only beginning to be understood. In this review, we update the information on astroglial modulation of the MeHg-induced neurotoxicity, providing remarks on their protective and deleterious roles and insights for future studies.